Affinity maturation generates pathogenic antibodies with dual reactivity to DNase1L3 and dsDNA in systemic lupus erythematosus - Eduardo Gomez-Bañuelos; Yikai Yu; Jessica Li; Kevin S. Cashman; Merlin Paz; Maria Isabel Trejo-Zambrano; Regina Bugrovsky; Youliang Wang; Asiya Seema Chida; Cheryl A. Sherman-Baust; Dylan P. Ferris; Daniel W. Goldman; et al. (Nature Communications, 2023)
Antibodies directed against DNA in systemic lupus erythematosus are functionally diverse. This study demonstrates that DNAse1L3 is the primary target of a subset of autoantibodies previously considered specific for double-stranded DNA.